Manipulating the NKG2D Receptor-Ligand Axis Using CRISPR: Novel Technologies for Improved Host Immunity - Alves, Eric; McLeish, Emily; Blancafort, Pilar; Coudert, Jerome D.; Gaudieri, Silvana (Frontiers in Immunology, 2021)
The activating immune receptor natural killer group member D (NKG2D) and its cognate ligands represent a fundamental surveillance system of cellular distress, damage or transformation. Signaling through the NKG2D receptor-ligand axis is critical for early detection of viral infection or oncogenic transformation and the presence of functional NKG2D ligands (NKG2D-L) is associated with tumor rejection and viral clearance. Many viruses and tumors have developed mechanisms to evade NKG2D recognition via transcriptional, post-transcriptional or post-translational interference with NKG2D-L, supporting the concept that circumventing immune evasion of the NKG2D receptor-ligand axis may be an attractive therapeutic avenue for antiviral therapy or cancer immunotherapy. To date, the complexity of the NKG2D receptor-ligand axis and the lack of specificity of current NKG2D-targeting therapies has not allowed for the precise manipulation required to optimally harness NKG2D-mediated immunity. However, with the discovery of clustered regularly interspaced short palindromic repeats (CRISPRs) and CRISPR-associated (Cas) proteins, novel opportunities have arisen in the realm of locus-specific gene editing and regulation. Here, we give a brief overview of the NKG2D receptor-ligand axis and discuss the levels at which NKG2D-L are regulated and dysregulated during viral infection and oncogenesis. Moreover, we explore the potential for CRISPR-based technologies to provide novel therapeutic avenues to improve and maximise NKG2D-mediated immunity.